Mulberry leaf polyphenols alleviated high-fat diet-induced obesity in mice - Li, Rui; Zhu, Qubo; Wang, Xiaoyan; Wang, Haiyan (Frontiers in Nutrition, 2022)
Mulberry leaf is an important medicinal food plant, which is rich in polyphenol compounds. Mulberry leaf polyphenols (MLP) possess significant lipid-loweringand antioxidant effects, and healthcare functions. In this study, the polyphenol content of mulberry leaf ethanol extract was measured using HPLC. The analysis of mulberry leaf extract resulted in the identification of 14 compounds, of which Chlorogenic acid and Quercitrin were the highest. A high-fat diet (HFD)-induced obese mouse model was developed and treated with MLP for 12 weeks to explore their effect on lipid metabolism in HFD-induced obese mice. The results showed that the MLP could inhibit the weight gain and fat cell volume increase in the HFD-induced obese mice in a dose-dependent manner. Further analysis revealed that the MLP decelerated the fatty acid composition in the adipose tissues of HFD-induced obese mice, and significantly increased the polyunsaturated-to-saturated fatty acid (PUFA/SFA) ratio. The real-time quantitative PCR(RT-qPCR) results indicated that the MLP significantly inhibited the down regulation of uncoupling protein (UCP) 1(UCP1), UCP3, and PR domain zincfinger protein 16(PRDM16) caused by the HFD. These beneficial effects of MLP on HFD-induced obese mice might be attributed to their ability to change the fatty acid composition of adipose tissue and increase the expression of thermogenesis genes. Overall, the study results suggested that the MLP could serve as potential lipid-lowering and weight-loss functional food and health care products.